Navigating English Learning via Heutagogical Approaches in Self-Directed Learning with Technology - Xuan, Zhicheng Dai; Xhu, Xiaoliang (Bright Institute, 2024)
Technology has created a demand for new learning methods in education, such as e-learning, blended learning, and flipped learning. Self-directed is one of the new learning approaches that functions primarily based on technological learning mediums. With the advent of technology, present-day learners can access several new learning mediums that expose them to language learning resources. This accessibility motivates the learners to choose the content, manage their learning activities, and assess what they learn with the support of technology. This study designs a tech-driven teaching-learning methodology by blending SDL with heutagogy and further aims to discover how much technological learning mediums help students in SDL. It also emphasizes the role of technology in developing SDL as a heutagogical approach to learning several components of the English language. A survey was conducted among the first-year engineering students of Anna University to collect data on using learning media in SDL regarding English Language Learning. Findings reveal that most students prefer technological learning mediums to learning by themselves. It also leads to the recommendation that students create awareness about SDL as a learning system that will help them promote self-paced learning.